Association of sodium intake with diabetes in adults without hypertension: evidence from the National Health and Nutrition Examination Survey 2009–2018 - Ming, Li; Wang, Duan; Zhu, Yong (Frontiers in Public Health, 2023)
Background: Sodium is essential for human health, however the prevalence of various diseases is associated with excessive sodium intake, particularly cardiovascular disorders. However, in most countries, salt intake is much higher than the World Health Organization recommends.Several studies in recent years have revealed that high salt intake is associated with diabetes in the general population, but the association is uncertain in people who don't have hypertension.In this study, we aimed to find out whether high sodium intake increases the risk of diabetes in this particular population.Method: Data were extracted from the National Health and Nutrition Examination Survey (NHANES; 2009-2018). Participants included adults aged over 20 years old who have undergone the diabetes questionnaire, and the hypertension population was excluded. In order to adjust the confounders, multivariate analysis models were built. Finally, subgroup analysis were conducted to investigate the association between sodium intake and diabetes separately. Result: In the present study, 7907 participants are included (3920 female and 3987 male), and 512 (6.48%) individuals reported diabetes. The median sodium intake of the participants was 3341 mg/d (IQR: 2498, 4364 mg/d). A linear association between sodium intake and the prevalence of diabetes was found (P=0.003). According to the multivariate analysis models, the odds ratio of diabetes for every 1000mg sodium intake increment is 1.20 (OR:1.20, 95% CI 1.07-1.35). The highest sodium intake quartile was 1.80-fold more likely to have diabetes than the lowest quartile (OR: 1.80, 95% CI 1.17-2.76). Conclusion: Our results suggest that higher sodium intake is associated with an increased risk of diabetes in the population without hypertension, and for every 1000mg sodium intake increment, the risk of diabetes increased by 1.20-fold. To sum up, we have provided the clue to the etiology of diabetes and further prospective research is needed to contribute recommendations for the primary prevention of diabetes in the US.